2002
DOI: 10.1002/pros.10136
|View full text |Cite
|
Sign up to set email alerts
|

Antigen‐specific tumor vaccine efficacy in vivo against prostate cancer with low class I MHC requires competent class II MHC

Abstract: BACKGROUND-Cancers can escape immune recognition by means of evading class I major histocompatibility complex (MHC) -mediated recognition by cytotoxic T lymphocytes. However, immunization strategies targeting defined tumor-associated antigens have not been extensively characterized in murine prostate cancer models. Therefore, we evaluated antigen-specific, antitumor immunity after antigen-encoding vaccinia immunization against mouse prostate cancer cells expressing a model tumor-associated antigen (β-galactosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…The effects of specific vaccinations are much less understood. So far, the results of the limited number of studies using well-defined experimental tumours in respect to their MHC class I status indicate that it is possible to induce effective immunity against MHC class I-deficient tumours at least with immunization protocols using cytokines or costimulatory molecules as adjuvants (17,(20)(21)(22)(23). The mechanisms underlying this immunity are not fully understood; they may include for example NK, Th cells and IFNÁ production (21,24).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of specific vaccinations are much less understood. So far, the results of the limited number of studies using well-defined experimental tumours in respect to their MHC class I status indicate that it is possible to induce effective immunity against MHC class I-deficient tumours at least with immunization protocols using cytokines or costimulatory molecules as adjuvants (17,(20)(21)(22)(23). The mechanisms underlying this immunity are not fully understood; they may include for example NK, Th cells and IFNÁ production (21,24).…”
Section: Introductionmentioning
confidence: 99%
“…Such presentation is central to initiate primary, cellular immune responses as well as to establish efficient, durable secondary immune responses (1,2). Although long known to mediate protective immunity to bacteria and toxins, the important roles of CD4 ϩ T cells in tumor immunity and viral clearance have also been well established (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…When CD4 + cells are stimulated and maintained, the CD8 + responses are sustained for long periods of time, improving the antitumor response, and potentially leading to the development of long-lasting immunological memory against tumor Ags. Recent studies have also shown the direct requirement for competent HLA class II pathway stimulation in the reduction of HLA class I-mediated response for an effective immunotherapy approach [ 18 , 70 , 71 ]. Furthermore, secondary stimulation following HLA class II-T cell receptor binding through costimulatory molecules is required for complete T cell stimulation.…”
Section: Hla Class II Processing In Prostate Cancer Cellsmentioning
confidence: 99%